A Textual Analysis of Imam Al-Baijuri’s Aswaja Theology: Doctrinal Reasoning in Two Primary Works - Hidayat, Muhammad; Mardiah, Ibnatul; Achmad, Nurcholik; Nasirin, Nasirin (Program Studi Aqidah dan Filsafat Islam, 2025)
This article offers a textual analysis of Imam Ibrāhīm al-Baijūrī al-Shāfiʿī’s Aswaja theology through close reading of two widely studied creedal works, Ḥāshiyah Kifāyah al-ʿAwām and Tuḥfat al-Murīd ʿalā Jawharat al-Tawḥīd. Positioned within the intellectual milieu of al-Azhar and post-classical Sunni kalām, the study first outlines al-Baijūrī’s scholarly profile and the basic conceptual foundations of Aswaja theology to clarify the doctrinal context in which his arguments operate. Methodologically, the research employs a qualitative descriptive–analytical library design and applies a structured textual coding procedure, using argumentative passages, technical terms, and chains of doctrinal reasoning as units of analysis. The discussion highlights how al-Baijūrī maintains an evidentiary balance between revelation (naql) and reason (ʿaql), assigning rational inquiry a bounded explanatory function without granting it autonomous authority over scriptural certainty. Three doctrinal loci receive focused analysis: (1) Ahl al-Fatrah, where definitive Qur’anic principles (qaṭʿī) guide the interpretation of speculative reports (ẓannī), supporting a restrained posture toward takfīr grounded in divine justice; (2) debates on the Qur’an as Kalāmullāh al-Qadīm, where the distinction between kalām nafsī and kalām lafẓī is used to reject both Muʿtazilite creationism and anthropomorphic literalism; and (3) the pedagogical articulation of divine and prophetic attributes (including the scheme of the “fifty attributes”), which connects doctrinal clarity to ethical orientation. The article concludes that al-Baijūrī’s Aswaja reasoning is characterized by conceptual precision and a consistent hierarchy of proofs, which helps explain why his thought is frequently associated with doctrinal moderation in later discourse.